THE INFLUENCE OF EDUCATION OF POSTPARTUM MOTHERS ON THE KNOWLEDGE OF POSTPARTUM RISK SIGNS - Meriem Meisyaroh Syamson; Harita (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2023)
One of the critical periods associated with maternal mortality risk is the postpartum period. Hence, it is imperative to prioritize postnatal care as a means to reduce maternal and infant mortality rates. According to the World Health Organization (WHO), approximately 30% of mothers face mortality risks during the puerperium. Unfortunately, many postpartum mothers are unaware of potential issues during this period, leading to delayed self-examinations with healthcare professionals. This lack of awareness stems from insufficient knowledge regarding the danger signs that may arise during the postpartum period. Previous study revealed that a significant number of mothers lack awareness about these danger signs during the puerperium. To enhance the knowledge of postpartum mothers, one effective approach is to provide education. This study aimed to investigate the impact of educational interventions on postpartum mothers' knowledge of danger signs during the postpartum period. The research employed a Quasi-Experimental design with a one-group pretest-posttest design. The sample consisted of 30 postpartum mothers, and all participants completed the entire study. Data collection involved administering a questionnaire both before and after the educational intervention. The Statistical Package for the Social Sciences (SPSS) was used for data analysis, and the Wilcoxon test was utilized with a significance level set at α < 0.05. Statistical analysis yielded a p-value of 0.000 (α < 0.05), indicating a statistically significant effect of education on increasing postpartum mothers' knowledge of danger signs during the puerperal period.